Dampak Judi Online Terhadap Kesehatan Mental Dan Hubungan Sosial - Sari, Arnit Kurnia; Al-Fajrih, Moh; Ahdiyanti, Istika (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2023)
The main aim of this research was to analyze how big the impact of online gambling is on mental health and social relationships in Sorong City, Southwest Papua. Online gambling has grown rapidly, but it cannot be ignored the impact it has on mental health and social relationships. The authors looked at the impact of online gambling on mental health and social relationships, and the findings suggest that engaging in online gambling can lead to addiction, anxiety, depression, and impaired social relationships. This problem is exacerbated by risk elements such as aggressive promotion and easy accessibility. It is important to gain a better understanding of these negative effects so that effective solutions can be developed.